2022
DOI: 10.3389/fbioe.2021.816980
|View full text |Cite
|
Sign up to set email alerts
|

YALIcloneNHEJ: An Efficient Modular Cloning Toolkit for NHEJ Integration of Multigene Pathway and Terpenoid Production in Yarrowia lipolytica

Abstract: Non-homologous end-joining (NHEJ)-mediated random integration in Yarrowia lipolytica has been demonstrated to be an effective strategy for screening hyperproducer strains. However, there was no multigene assembly method applied for NHEJ integration, which made it challenging to construct and integrate metabolic pathways. In this study, a Golden Gate modular cloning system (YALIcloneNHEJ) was established to develop a robust DNA assembly platform in Y. lipolytica. By optimizing key factors, including the amounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…It is sometimes easier to construct gene expression libraries relying on NHEJ. In some cases, NHEJ even plays an important role in gene integration. ,, However, the stochasticity of integration sites and copy numbers in NHEJ causes difficulty for precise optimization of synthetic pathways . Genome editing tools that rely on HR are difficult to function in Y. lipolytica .…”
Section: Development Of Synbio Tools For Y Lipolyticamentioning
confidence: 99%
See 1 more Smart Citation
“…It is sometimes easier to construct gene expression libraries relying on NHEJ. In some cases, NHEJ even plays an important role in gene integration. ,, However, the stochasticity of integration sites and copy numbers in NHEJ causes difficulty for precise optimization of synthetic pathways . Genome editing tools that rely on HR are difficult to function in Y. lipolytica .…”
Section: Development Of Synbio Tools For Y Lipolyticamentioning
confidence: 99%
“…After overexpressing the whole MVA pathway, the titer of αhumulene was increased by 30 times, 32 the titer of β-ionone was increased by 43.7 times, 66 and the titer of (−)-α-bisabolol was increased by as much as 97 times. 36 However, integrative overexpression of the entire MVA pathway is a challenge due to the low HR efficiency of Y. lipolytica. Therefore, most researchers chose to manipulate only the key genes.…”
Section: Engineering the Terpenoid Skeleton (C5) Synthesis Module 321...mentioning
confidence: 99%
“…Isopentenyl diphosphate isomerase (IDI) is a key node for balancing the amount of IPP and DMAPP. Accordingly, its overexpression can also improve the precursor supply. , Combinatorial expression of these key genes can be achieved using the Golden Gate modular cloning system based on nonhomologous end-joining . Another strategy to enhance the flux through the MVA pathway is to overexpress the endogenous transcription activator UPC2, which is unique in S. cerevisiae .…”
Section: Pathway Engineering For Terpene Biosynthesis In Yeastsmentioning
confidence: 99%
“…13,95 Combinatorial expression of these key genes can be achieved using the Golden Gate modular cloning system based on nonhomologous endjoining. 96 Another strategy to enhance the flux through the MVA pathway is to overexpress the endogenous transcription activator UPC2, which is unique in S. cerevisiae. Binding to UPC2 binding sites in natural promoters of MVA pathway genes enhances enzyme expression at the transcriptional level.…”
Section: Optimizing the Terpene Precursor Synthesis Pathwaysmentioning
confidence: 99%
“…Shi et al overexpressed the entire MVA pathway genes in Y. lipolytica to increase the metabolic flux to FPP and optimize the copy number of MrBBS and tHMG1 , resulting in the production of 4.4 g/L in a 5 L bioreactor. This was the highest production in yeast reported to date [ 14 ]. A recent study showed that overexpression of tHMG1 , ERG10 , and ACS1 lead to a 13-fold increase in (–)-α-bisabolol biosynthesis in S. cerevisiae , but the final production was only 124 mg/L [ 11 ].…”
Section: Introductionmentioning
confidence: 99%